Parametric study of laser‐induced graphene conductive traces and their application as flexible heaters. (30th March 2021) - Karimi, Gholamreza; Lau, Irene; Fowler, Michael; Pope, Michael
Summary: Laser‐scribed carbonization of polyimide (PI), also known as laser‐induced graphene (LIG), has been used to fabricate flexible and conductive traces on polymer films. With the assistance of electrical tests, scanning electron microscopy (SEM) and Raman spectrometry, a systematic procedure, was used to investigate the effect of laser operating parameters (laser power, scanning speed, and pitch) on the electrical properties, morphology, and thermal performance of the laser scribed carbonized circuits. Identifying the laser optimum operation conditions, flexible heaters with various thermal patterns are produced directly on the PI films and their electro‐thermal performance was evaluated. Although the experimental results indicated anisotropic behavior of the laser‐induced carbonized traces, with regard to in‐plane vs through‐plane conductivity, the optimized heaters demonstrated a rapid response time, reaching equilibrium within less than 60 seconds and being able to achieve temperatures upward of 90°C using relatively low DC voltages of 6 to 24 V. These promising attributes and the demonstrated ability to pattern small features (<100 μm) rapidly and into arbitrary designs make the approach ideal for applications where space and weight are critical factors such as in microfluidics, aerospace, and defense, especially when compared to traditional heaters made from metals which are heavier and more complicated to pattern.